Borate binding to polyol-stabilized latex - Pelton, Robert (Langmuir : the ACS journal of surfaces and colloids, 2011)
Borate or 4-carboxyphenylboronate anions condense with diol units on poly(glycerol monomethacrylate) stabilizer chains at the surface of polystyrene latex, increasing the latex charge density. Combining Leibler's equilibrium binding model with Ohshima's hydrogel electrophoresis model simulated the primary experimental observation: the electrophoretic mobility of this latex becomes much more negative above pH 9.5 because of borate anion binding. There is an unusual inverse relation between the electrophoretic mobility and the density of borate anions bound to the latex particles. Very high solution concentrations of borate ions and hence high ionic strengths are required to give high densities of bound borate ions. Thus, mobilities decrease in spite of increasing charge density with borate addition because of increased screening at high ionic strength